How exporters grow - Doireann Fitzgerald; Stefanie Haller; Yaniv Yedid-Levi (University College Dublin, UCD School of Economics, 2017)
We document how export quantities and prices evolve after entry to a market. Controlling for marginal cost, and taking account of selection on idiosyncratic demand, there are economically and statistically significant dynamics of quantities, but no dynamics of prices. To match these facts, we estimate a model where firms invest in customer base through non-price actions (e.g. marketing and advertising), and learn gradually about their idiosyncratic demand. The model matches quantity, price and exit moments. Parameter estimates imply costs of adjusting investment in customer base, and slow learning about demand, both of which generate sluggish responses of sales to shocks.
Keywords: 330